ESENSI METODE MONTESSORI DALAM KURIKULUM PENDIDIKAN ANAK USIA DINI - Asyruni Multahada (Samawa (Sakinah, Mawaddah Warahmah), 2021)
The Montessori method has been widely applied by teachers and even parents in providing education to early childhood. According to Montessori, children's education must be in accordance with the stages of child development. The Montessori view of children's education cannot be separated from the influence of other experts' thoughts, which emphasize the condition of a free and loving environment so that children's potential can develop optimally. The essence of the Montessori method in the PAUD curriculum includes all education, namely self-education, freedom, order, and the development of the senses. Meanwhile, the essence of the Montessori method based on the stages of development includes the Absorbent Mind, The Sensitive Periods, Children Want to Learn, Stages of Development, and Encouraging Independence.